The vacationers - Straub, Emma (Riverhead Books, a member of Penguin Group (USA), 2014)
Celebrating their thirty-fifth anniversary and their daughter's high-school graduation during a two-week vacation in Mallorca, Franny and Jim Post confront old secrets, hurts, and rivalries that reveal sides of themselves they try to conceal.